Indian Journal of Nematology 14(1): 1984 (Indian Journal of Nematology, 2024)
EDITORIAL BOARD (1984-86)Editor-in-Chief         - GOPAL SWARUP, Nematology Divn., LA.R.I., New DelhiEditor                         - D.R. DASGUPTA, Nematology Divn., LA.R.I., New DelhiMembers                   - P.K. KOSHY, Kayangulam                                     - Y.S. RAo, Cuttack                                     - B.S. YAPAV, Udaipur                                     - S.K. SAXENA, Aligarh